Eugenics and Modern Biology: Critiques of Eugenics, 1910-1945 - Allen, Garland E (2011)
Eugenics in most western countries in the first four decades of the twentieth century was based on the idea that genes control most human phenotypic traits, everything from physical features such as polydactyly and eye color to physiological conditions such as the A-B-O blood groups to mental and personality traits such as “feeblemindedness”, alcoholism and pauperism. It assessing the development of the eugenics movement – its rise and decline between 1900 and 1950 – it is important to recognize that its naïve assumptions and often flawed methodologies were openly criticized at the time by scientists and non-scientists alike. This paper will present a brief overview of the critiques launched against eugenicists’ claims, particularly criticisms of the American school led by Charles B. Davenport. Davenport’s approach to eugenics will be contrasted to his British counterpart, Karl Pearson, founder and first editor of Annals of Eugenics. It was not the case that nearly everyone in the early twentieth century accepted eugenic conclusions as the latest, cutting-edge science. There are lessons from this historical approach for dealing with similar naïve claims about genetics today